2002
DOI: 10.1179/003258902225002460
|View full text |Cite
|
Sign up to set email alerts
|

Sintering behaviour and mechanical properties of PM Al-Zn-Mg-Cu alloy containing elemental Mg additions

Abstract: Zn, and Si, which are all soluble in aluminium. For every chemical composition of these alloys it is thus essential to A commercially available PM Al-5•5Zn-2•5Mg-1•6Cu point out that liquid phase sintering promotes the basic (wt-%) alloy has been used to study the eVect of mechanisms for neck formation, the development of the elemental Mg additions, ranging from 0 to 4•5 wt-%, alloys and constitution of their microstructure. Speci c on its sinterability and mechanical properties after chemical compositions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 9 publications
2
34
0
2
Order By: Relevance
“…[7][8][9][10] On the other hand, major improvement on sinterability of Al alloys (primarily 7xxx and 2xxx series) containing Pb, Sn and Sb have been achieved through liquid phase sintering. [11][12][13][14][15][16] Silicon is one addition that is now commonly used due to several property gains. 17 To increase the elastic modulus, it is common to incorporate hard ceramic phases such as SiC, Al 2 O 3 or B 4 C. 17 This paper uses the Taguchi design of experiments approach to characterise the press sinter response of an Al-6061 alloy powder produced by rapid solidification.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] On the other hand, major improvement on sinterability of Al alloys (primarily 7xxx and 2xxx series) containing Pb, Sn and Sb have been achieved through liquid phase sintering. [11][12][13][14][15][16] Silicon is one addition that is now commonly used due to several property gains. 17 To increase the elastic modulus, it is common to incorporate hard ceramic phases such as SiC, Al 2 O 3 or B 4 C. 17 This paper uses the Taguchi design of experiments approach to characterise the press sinter response of an Al-6061 alloy powder produced by rapid solidification.…”
Section: Introductionmentioning
confidence: 99%
“…Fax: +902642956424. this reason enhanced the mechanical features (Kondoh et al, 2001). The new scientists (Martin et al, 2002) have concluded that rising the Mg content equal to 3.5 wt % in 7xxx series enhanced the mechanical strength better than the present commercial alloy. Moreover, it was mentioned (Lumley and Schaffer, 1996) that at elevated Mg contents, the inferior phase could not be completely dissolved in solid solution and therefore stayed as a complex at the grain boundaries resulting embrittlement of the alloy.…”
Section: Introductionmentioning
confidence: 73%
“…This was feasible by a liquid phase sintering (LPS) course resulting to enhance densification of the alloys. In the reported papers, the cause of trace addition of chosen elements such as Pb, Sn and Sb on the sinterability of Al alloys was examined (Martin et al, 2002;Lumley and Schaffer, 1996;Schaffer et al, 2001;Schaffer and Huo, 1999;Sercombe and Schaffer, 1999;Sercombe, 2003). It was understood that microalloying with 100 ppm of Pb (0.12 wt% Pb) supplied the superlative sintering reaction and enhanced the ultimate tensile strength (UTS) by 36% from 214 to 427 MPa of an Al-Zn-Mg-Cu alloy formed from premixed elemental powders (Sercombe, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…An essential requirement for effective liquid phase sintering is a wetting liquid. Based on thermodynamically approach, magnesium reacts with aluminium oxide forming spinel, facilitating the disruption of oxide layer and thus wetting by liquid (Ziani & Pelletier, 1999); (Martín et al, 2002); (Martín & Castro, 2003). The reaction may be facilitated during sintering by diffusion of the magnesium through the aluminium matrix and will be accompanied by a change in volume, creating shear stresses in the film, ultimately leading to its break up.…”
Section: Introductionmentioning
confidence: 99%